Anti-“Heterosexist” Education and the Stigmatization of Some Roman Catholic Beliefs - Jordan, M. (Philosophical Inquiry in Education, 2018)
I address some tension between Roman Catholicism and the anti-“heterosexist” education within some of Ontario’s regular, public schools. In particular, I argue that the anti-“heterosexist” education within the Peel District School Board (PDSB) and the Toronto District School Board (TDSB) stigmatizes some Roman Catholic beliefs, however incidentally. I then offer a proposal for how this stigmatization could be extinguished without abandoning an effort to prevent bullying against students with same-sex sexual inclination.